A Study on Treatment Compliance among Methadone Clients in MMTP Program TUTH, Nepal - Dangol, Kabin Man; Chapagain, Manisha; Tulachan, Pratikchya (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 50-56 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8806